2008
DOI: 10.1002/qua.21808
|View full text |Cite
|
Sign up to set email alerts
|

A DFT study of transformation of nitrosothiol isomers and their decomposition to nitric oxide in gas phase

Abstract: ABSTRACT:The structures of nitrosothiol isomers were obtained by geometry optimizations using the density functional theory calculations. Two cis-isomeric, 2 transisomeric, and 1 zwitterionic species of the HSNO isomers were found and the most stable species is the trans-isomer. Energetics, thermodynamic properties, rate constants, equilibrium constants of all transformation reactions, and their energy profiles were obtained. Decomposition of the HSNO trans-isomer to nitric oxide was investigated and its rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…As the B3LYP/6-31G(d) basis set used for sulfur atom was examined compared with 6-311? ?G(d,p) and aug-ccpVQZ basis sets in the structure optimization of the nitrosothiol [28], it was found that the B3LYP/6-31G(d)-optimized structure data were acceptable as closed to its structures optimized using B3LYP/6-311?G(d,p) and B3LYP/6-311? ?G(d,p) methods.…”
Section: Methodsmentioning
confidence: 97%
“…As the B3LYP/6-31G(d) basis set used for sulfur atom was examined compared with 6-311? ?G(d,p) and aug-ccpVQZ basis sets in the structure optimization of the nitrosothiol [28], it was found that the B3LYP/6-31G(d)-optimized structure data were acceptable as closed to its structures optimized using B3LYP/6-311?G(d,p) and B3LYP/6-311? ?G(d,p) methods.…”
Section: Methodsmentioning
confidence: 97%
“…The rate constant k (T), based on transition state theory, was computed from the Gibbs free energy of activation, Δ † G o Scheme 1 Plausible pathways of peptide bond cleavage due to hydrolytic reactions [14] (1) [42,43] and the activation energy, Δ † E o using Eq. (2) [44].…”
Section: Methodsmentioning
confidence: 99%
“…Q TS and Q REA are the partition functions of the transition state and reactant of the reaction, whose values are composed of translational, rotational, and vibrational partition functions. The tunneling coefficient (κ) can be computed with the Wigner method [43,[45][46][47] as…”
Section: Methodsmentioning
confidence: 99%
“…The rate constants k(T) for reactions of the ethanol conversion to ethylene derived from the transition-state theory were computed from activation energy ( ‡ E) using Eq. (1) [47,48].…”
Section: Thermodynamic Properties and Formation Constantsmentioning
confidence: 99%